N=90 QSPT: Cerium, neodymium and samarium isotopic chains in the IBM symmetry triangle - Koseoglou, P.; Werner, V.; Pietralla, N.; Bonatsos, D. (HNPS Advances in Nuclear Physics, 2019)
The even-even nuclei, near the the N=90 quantum shape phase transition, of cerium, neodymium and samarium isotopic chains were placed in the interacting boson model symmetry triangle. The different trajectories of the chains revealed the increasing γ-dependence from samarium to cerium by decreasing Z, which can be associated with the decreasing sharpness of the transition from spherical to deformed structures.